Vitamin B12 as an epidrug for regulating peripheral blood biomarkers in long COVID-associated visuoconstructive deficit - Larissa M. G. Cassiano; Jonas J. de Paula; Daniela V. Rosa; Débora M. Miranda; Marco A. Romano-Silva; Roney S. Coimbra (Scientific Reports)
Abstract Approximately four months after recovering from a mild COVID-19 infection, around 25% of individuals developed visuoconstructive deficit (VCD), which was found to be correlated with an increase in peripheral immune markers and alterations in structural and metabolic brain imaging. Recently, it has been demonstrated that supplemental vitamin B12 regulates hyperinflammation during moderate and severe COVID-19 through methyl-dependent epigenetic mechanisms. Herein, whole peripheral blood cultures were produced using samples obtained from patients with confirmed persistent VCD, and controls without impairment, between 10 and 16 months after mild COVID-19. This experimental model was used to assess the leukocyte expression patterns of 11 biomarkers previously associated with VCD in long COVID and explore the potential of pharmacological B12 in regulating these genes. The results showed that patients with persistent VCD displayed continued upregulation of CCL11 and LIF compared to controls. It is worth noting that elevated serum levels of CCL11 have been previously linked to age-related neurodegenerative diseases. Notably, the addition of 1 nM of vitamin B12 to blood cultures from individuals with VCD normalized the mRNA levels of CCL11, upregulated the neuroprotective HGF, and, to a lesser extent, downregulated CSF2 and CXCL10. There was an inverse correlation observed between CCL11 mRNA levels and methylation levels of specific cytosines in its promoter region. These findings underscore the significance of systemic inflammation in persistent VCD associated with long COVID. Moreover, the study provides evidence suggesting that B12, acting as an epidrug, shows promise as a therapeutic approach for addressing this cognitive impairment.